Importância da Inércia Higroscópica em Museus - Cláudia Sofia Faia Miranda Ferreira (2008)
Moisture is one of the main causes of deterioration in buildings, especially the variations in relative humidity of the indoor air. In buildings that are used for special purposes, such as museums, and which do not have permanent air-conditioning systems, these variations in relative humidity may affect the works of art kept in their collections.The Laboratory of Building Physics (LFC) of the Faculty of Engineering, University of Oporto (FEUP), has been engaged in important research in the area of Hygroscopic Inertia. Its recent participation in the international research project Annex 41- Whole Building Heat, Air and Moisture, organised by the International Energy Agency, has contributed to significant advances in the control of indoor hygrothermal conditions in a museum, with sole and exclusive recourse to the building.The aim of this work is to analyse and assess the hygrothermal conditions of a museum that is not equipped with permanent air-conditioning, and, by experimental research, study the passive effect of the building on the control of indoor hygrothermalconditions.It goal to prove that the use of hygroscopic materials in museum's interior finishing contributes to the control of hygrothermal conditions, a principle which, it is hoped, may be applied to the adaptive rehabilitation of museums located in old buildings.KEYWORDS: Relative Humidity, Museums, Hygroscopic Inertia.